Is Intraoperative Ultrasound Required in Cervical Spinal Tumors? A Prospective Study - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2012)
AIM: To determine the role of intraoperative ultrasonography (IOUSG) in the surgical management of patients with intradural spinal tumors. MATERIAL and METHODS:Twenty-six patients with intradural spinal cord tumors were surgicallytreated under intraoperative ultrasonographic guidance between January 2007 and May 2011. Guidance with IOUSG was used in 26 patients, of which 14 fourteen had extramedullary and 12 had intramedullary tumors. Intraoperative ultrasound assistance was used to localize each tumor exactly before opening the dura. The extent of tumor resection was verified using axial and sagittal sonographic views. The extent of tumor resection achieved with IOUSG guidance was assessed on postoperative early control MRI sections. RESULTS: Total tumor resection was achieved in 22 (84%) of 26 cases. All of the residual tumors were typically intramedullary and infiltrative. The sensitivity of IOUSG for the determination of the extent of resection was found to be 92%. Ultrasonography was found to be effective in identification of tumor boundaries and protection of spinal cord vessels. The average time spent for IOUSG assessment was 7 minutes. CONCLUSION: Intraoperative ultrasonography is practical, reliable and highly sensitive for spinal cord surgery. It not only enhances surgical orientation, but also reduces morbidity and helps to resect the tumor completely.
Keywords: Intraoperative; Ultrasonography; Spinal cord; Tumor; SONOGRAPHY; SURGERY; CORD